Anaerobic Co-Digestion of Palm Oil Effluent and Food Waste - Samuel,Batet and Okuma Silas Oseme (NIPES - Journal of Science and Technology Research, 2023)
The yearly expansion of oil palm plantations in Nigeria is accompanied by an increase in the number of palm oil mills that produce crude palm oil (CPO) from fresh fruit bunches (FFB). In Okada alone, there are several palm oil mills, and Igbinedion University just acquired a palm oil farm that is currently undergoing development. The production process in a palm oil mill consists of sterilization, stripping, clarification, and palm kernel oil recovery. This generates solid waste and liquid waste. The liquid waste (i.e., palm oil effluent), when discharged directly into the environment without proper treatment, can pollute the environment, emitting greenhouse gases (GHG) that cause global warming. In this study, palm oil mill effluent and food waste were evaluated for biogas production under. Food waste and palm oil effluent from Okada town were co-digested in a fixed dome anaerobic digester at a mesophilic temperature range. The highest cumulative biogas yield was achieved from the co-digestion of palm oil effluent and food waste. Besides, the digestates obtained at the end of the complete hydraulic retention time were odourless, which is an indication of thorough treatment of the palm oil effluent. More so, such digestates can serve as organic manure for Okada palm oil farms.
NIPES Proceedings in Science and Technology: 2nd International Conference, 2023 ISSN: 3121-9861
Keywords: Palm oil effluent; Food waste; co-digestion; biogas yield; mesophilic temperature